Measuring teacher creativity-nurturing behavior and readiness for 21st century classroom management - Jaggil Apak; Muhamad Suhaimi Taat; Norazah Mohd Suki (IGI Publishing, 2021)
The COVID-19 pandemic is drastically reshaping the 21st century classroom management to remote learning via various online teaching and learning platforms across the world. The aims of this study are threefold: to assess the level of creativity nurturing behavior and teacher readiness for 21st century classroom management, to test the differences of this relationships towards teaching experience, and to examine the relationship between teachers’ creativity nurturing behavior and their readiness for 21st century classroom management. The ANOVA test revealed that teachers’ creativity-nurturing behavior is significantly different according to teaching experience. What’s more, regression analysis revealed that teachers’ creativity-nurturing behavior affects their readiness for 21st century classroom management. Teachers should stimulate positive changes in pedagogical practice to transform the classroom into a more active learning community with greater potential for creativity. Direction for future research is also furnished